Urban transformation in airport regions. - Scholl, Bernd; Nebel, Reto (Routledge, 2014)
Using the development of Zurich Airport as an example, one process is presented and conclusions concerning future processes are drawn from it. The case study makes it clear that spatial planning is being called upon to proactively engage with the development of high-density traffic airports. In particular, technological advances in aircraft manufacture to reduce noise emissions, as well as innovative landing and take-off procedures, open new perspectives to mitigate the central conflicts in airport and spatial development. The importance of assessing the potential for settlement redevelopment in airport regions is a significant conclusion.
Keywords: Stadtplanung; Flughafen; Flughafenplanung; Städtebauliche Einordnung; Standort; Lärmschutz; Fluglärm; Technische Entwicklung; Flugzeug; Fahrzeugtechnik; Lärmreduzierung; Transformation